An evaluation of invasive fungal sinusitis outcomes with subsite analysis and use of frozen section analysis. Issue 8 (7th June 2016) - Foshee, James; Luminais, Chris; Casey, James; Farag, Alexander; Prestipino, Anthony; Iloreta, Alfred Marc; Nyquist, Gurston; Rosen, Marc
Abstract : Background: Invasive fungal sinusitis (IFS) is an aggressive mycosis of the nasal cavity with frequent extension to adjacent structures. Occurring more commonly in immunocompromised individuals, prognosis is typically poor despite aggressive treatment. This study aims to examine postoperative outcomes and survival of a cohort of fungal sinusitis patients at an academic center, as well as identify causes of death in IFS patients. Methods: This study was a retrospective chart review of patient charts and departmental records, yielding patient demographics, medical and surgical treatments, pathology records, and outcomes data. Results: Twenty‐seven patients were identified from departmental records between 1998 and 2014. Twenty‐one patients presented with Mucor infections, whereas the remaining 6 patients had Aspergillus . All patients were immunocompromised: diabetes (n = 14) and hematologic malignancy (n = 13). Three patients had multiple causes of immunosuppression. Most commonly involved subsites were the maxillary, ethmoid, and sphenoid sinuses. Nasal septum involvement was independently associated with mortality ( p < 0.01). Overall mortality was 57.7% within 1 year, although 66.7% of fatalities occurred within 1 month of diagnosis. Conclusion: Overall survival for IFS remains poor. Widespread disease and nasal septum involvement were associated with a negative clinical course. Early identification and aggressive surgical and antifungal therapy is warranted. Even despite intense therapy, comorbid conditions and drug toxicity increase mortality and complicate the clinical course.